2002
DOI: 10.1097/00004770-200202000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Canal Contents on the Electrical Assisted Determination of the Length of Root Canals

Abstract: The purpose of this study was to compare the influence of the root canal status on the determination of the root canal length by an electronic apex locator in vital and necrotic canals and canals with root canal filling retrieval. One hundred seven teeth with a total of 171 canals with various contents (105 vital pulp, 47 necrotic pulp, and 19 retrieval of root canal filling materials) were measured for root canal length in vivo with the AFA Apex Finder. The distance between the file tip and the radiographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 16 publications
2
31
0
2
Order By: Relevance
“…Although some authors 8,24 have demonstrated a higher accuracy of EFLs in determining WL in vital canals, when compared with necrotic canals, the identical accuracy found in our sample regardless of pulp condition is in agreement with other studies. [5][6][7]9,10 The rate of acceptable measurements (73.61%), considering both vital and necrotic pulps, indicates that the NovApex  EFL is accurate and useful to determine WL under clinical circumstances.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although some authors 8,24 have demonstrated a higher accuracy of EFLs in determining WL in vital canals, when compared with necrotic canals, the identical accuracy found in our sample regardless of pulp condition is in agreement with other studies. [5][6][7]9,10 The rate of acceptable measurements (73.61%), considering both vital and necrotic pulps, indicates that the NovApex  EFL is accurate and useful to determine WL under clinical circumstances.…”
Section: Discussionsupporting
confidence: 93%
“…endodontics, [4][5][6][7][8][9][10][11][12][13] has some advantages, e.g. the possibility to study root canal anatomy and to identify periapical lesions, as reported by ElAyouti et al 14 Conversely, one disadvantage of this method is related to the difficulties involved in locating the apical foramen and the apical constriction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their statistical analyses suggested that these two values were significantly different from one another. Unlike Dunlap et al's study, 34 the findings of Pommer et al 37 suggest that third generation EAL work better in vital canals than necrotic canals. This makes sense from an impedance change (at the AC) point of view.…”
Section: Third Generation Electronic Apex Locators (Tgeals) (Fig 2)mentioning
confidence: 67%
“…Pommer at al. 37 reported that it correctly identified the position of the AC in 94% of vital canals, but only 77% of the time in necrotic canals. Their statistical analyses suggested that these two values were significantly different from one another.…”
Section: Third Generation Electronic Apex Locators (Tgeals) (Fig 2)mentioning
confidence: 99%